1997
DOI: 10.2307/3433873
|View full text |Cite
|
Sign up to set email alerts
|

Renal Effects of Environmental and Occupational Lead Exposure

Abstract: Environmentl and industrial lead exposurs coninue t pose major public health problems in children and in adults. Acute

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 74 publications
(98 reference statements)
3
45
0
Order By: Relevance
“…They suggested that those indicators were the most sensitive and useful for renal dysfunction investigation. (Endo et al 1990(Endo et al , 1993Chia et al 1995;Loghman-Adham 1997;Jung et al 1998). …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…They suggested that those indicators were the most sensitive and useful for renal dysfunction investigation. (Endo et al 1990(Endo et al , 1993Chia et al 1995;Loghman-Adham 1997;Jung et al 1998). …”
Section: Discussionmentioning
confidence: 97%
“…Saturnine gout is a consequence of decreased tubule function (Zenz 1994). The development of gout appears to be a common feature of lead nephropathy (Loghman-Adham 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An association between lead poisoning and renal disease in humans has been recognized for over a century [1,2]. Renal manifestations of acute lead poisoning include glycosuria, aminoaciduria, and phosphaturia, collectively representing the Fanconi syndrome [2±5].…”
Section: Introductionmentioning
confidence: 99%